Mental health outcomes of balneotherapy: a systematic review. Issue 1 (2nd January 2021) - Clark-Kennedy, James; Kennedy, Gerard; Cohen, Marc; Conduit, Russell
ABSTRACT: Hot springs bathing is a 56 billion commercial industry worldwide, and systematic reviews suggest hot springs bathing (balneotherapy – BT) has a positive impact on chronic pain and musculoskeletal conditions, yet there are no known reviews on BT and mental health issues such as depression, anxiety, and stress. PRISMA guidelines were followed and the Scopus, PubMed, CINAHL, and Embase databases were examined during May 2020 using search terms to identify English language studies on BT and mental health. The included studies involved a controlled trial of bathing in geothermal mineral water with a no bathing, placebo, or active control group and reported any outcome related to mental health. Of 570 studies, 22 articles (1997–2019) were included. Depression, sleep problems, and stress were all seen to improve and anxiety improved in some but not all studies. BT is a fast-growing worldwide industry and has been shown to positively impact sleep, stress, anxiety, and depression. This has implications for the use of BT as a valid complementary therapy for people with mental health conditions. However, future clinical research is required to determine the populations likely to receive the most benefit from BT and distinguish factors that contribute to positive effects.